(untitled) (Atlanti +, 2026)
Purpose: Presidential records define and amplify the relationship that exists between the governing and the governed. As such, they should be treated as public records in the broad interest of transparency and accountability to promote good governance. The tumultuous events recently witnessed at the National Archives and Records Administration in the United States of America should be an eye opener to the global archives community and provide a window of opportunity to advance the cause for archives. Evidence management has been at the epicentre of the archival profession since time immemorial as this defines who we are as archivists and this piece attempts to highlight this as it dissects this watershed moment in archival discourse. An attempt is also made to draw lessons from this incident for the benefit of archival institutions within the East and Southern African region and to reignite the contentious debate on archival ethics. Methods: This is a desktop study that qualitatively draws on a review of relevant archival scholarship and online publications. A desk top study also knows as a desk study is a research method that involves collecting, reviewing and analysing existing information and data from secondary sources without fieldwork. Results: The findings highlight the vulnerability of the records profession to the whims of politicians in view of the evidence that recordkeepers protect in these records. These insights underscore the broader challenges faced by the recordkeeping profession in managing records of a country’s leader. The sanctity of evidence is what makes our calling as archivists as we are guardians of the 1 Assoc. Prof. Francis Garaba, Information Studies Department, University of KwaZulu-Natal (UKZN), email: garaba@ukzn.ac.za. 2 NB. This paper attempts to provoke discussion of archival issues (presidential records) and re-ignite the debate on archival ethics and is an original article not submitted to any publication. truth. Enacting specific legislation that informs the management of presidential records could help solve this conundrum especially for archival institutions within ESARBICA. Discussion: By interrogating President Trump’s destabilization of the recordkeeping profession, this article assesses the seismic professional impact it has had. The incident highlights several lessons that can be drawn from this event which inter alia include the need to enact specific legislation that informs their stewardship and re-ignites the contentious debate on archival ethics. Lastly, it is argued in this article that this incident provides a window of an opportunity from an advocacy point of view for us to defend the recordkeeping profession as we need an evidence management campaign in this regard.